2018
DOI: 10.1093/jcag/gwy025
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Suicide in Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis

Abstract: Background and Aims Patients with inflammatory bowel disease (IBD) have higher incidence of psychosocial disorders, including depression. As suicide is the most severe manifestation of depression, we sought to identify if patients with IBD have a higher incidence of suicide through a systematic review and meta-analysis. Methods Systematic literature searches for articles using EMBASE and MEDLINE using Ovid were conducted to identify studies investigating suicide in IBD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
2
16
0
3
Order By: Relevance
“…17 Psychological care in IBD (Australian IBD Standard A13) Level of distress. The mean level of distress for these respondents (K10 = 20.9) was within the mild distress category (20)(21)(22)(23)(24), while 51% of respondents reported good mental health (K10 score < 20), and 15% reported severe distress (K10 score ≥ 30) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Psychological care in IBD (Australian IBD Standard A13) Level of distress. The mean level of distress for these respondents (K10 = 20.9) was within the mild distress category (20)(21)(22)(23)(24), while 51% of respondents reported good mental health (K10 score < 20), and 15% reported severe distress (K10 score ≥ 30) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, while good‐quality data on suicide in IBD in Australia are not available, a large‐scale American study ( n = 2 325 226) showed that 27% of people with IBD and depression reported suicidal ideation versus 12% of those without depression . A recent meta‐analysis indicated that people with IBD may have increased risk of suicide . Psychological screening is an Australian standard of care for all people with IBD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Az öngyilkossági rizikó IBD-s fiatalok körében a három leggyakoribb, mortalitást jelentő ok között szerepel egy skandináv vizsgálat szerint [24]. A Zhang és mtsai által publikált metaanalízis alapján a IBD-vel élők körében magasabb öngyilkossági rizikó feltételezhető az átlagnépességhez képest [25].…”
Section: Megbeszélésunclassified
“…In this issue of JCAG, a systematic review and meta-analysis of suicide in IBD is reported (13). The analysis was mostly negative.…”
mentioning
confidence: 99%